2019
DOI: 10.3389/fgene.2019.00465
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Impact of a Novel CFH Splice Site Variant in Atypical Hemolytic Uremic Syndrome

Abstract: Atypical hemolytic uremic syndrome (aHUS) is a heterogeneous disorder characterized by microangiopathic hemolytic anemia (MAHA), thrombocytopenia, and acute kidney injury (AKI). In about 50% of cases, pathogenic variants in genes involved in the innate immune response including complement factors complement factor H (CFH), CFI, CFB, C3, and membrane co-factor protein (MCP/CD46) put patients at risk for uncontrolled activation of the alternative complement pathway. As aHUS is characterized by incomplete penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Gene mutations and related proteins encoded by these genes play an important role in the course of the disease. Genetic studies in these patients do not include large series [ 12 ]. Venables et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene mutations and related proteins encoded by these genes play an important role in the course of the disease. Genetic studies in these patients do not include large series [ 12 ]. Venables et al .…”
Section: Introductionmentioning
confidence: 99%
“…Gene mutations and related proteins encoded by these genes play an important role in the course of the disease. Genetic studies in these patients do not include large series [12]. Venables et al [13] previously showed, in a family with aHUS that non allelic homologous recombination results in the formation of a hybrid gene derived from exons 1-21 of CFH and exons 56 of CFHR1.…”
Section: Introductionmentioning
confidence: 99%